ITT9132 Concrete Mathematics Lecture 5 25 February 2019

ITT9132 Concrete Mathematics Lecture 5 25 February 2019

Sums ITT9132 Concrete Mathematics Lecture 5 25 February 2019 Chapter Two Finite and Innite Calculus Derivative and Dierence Operators Integrals and Sums Summation by Parts Innite Sums Contents 1 Finite and Innite Calculus Derivative and Dierence Operators Integrals and Sums Summation by Parts 2 Innite Sums Next section 1 Finite and Innite Calculus Derivative and Dierence Operators Integrals and Sums Summation by Parts 2 Innite Sums Next subsection 1 Finite and Innite Calculus Derivative and Dierence Operators Integrals and Sums Summation by Parts 2 Innite Sums Derivative and Dierence Operators Innite calculus: derivative Finite calculus: dierence Euler's notation ∆f (x) = f (x + 1) − f (x) f (x + h) − f (x) Df (x) = lim In general, if h 2 (or h 2 ), then h!0 h R C Forward dierence Lagrange's notation ∆h [f ](x) = f (x + h) − f (x) 0 f (x) = Df (x) Backward dierence [f ](x) = f (x) − f (x − h) Leibniz's notation If y = f (x), then Oh dy df df (x) dx = dx (x) = dx = Df (x) Central dierence d [f ](x) = Newton's notation h f (x + 1 h) − f (x − 1 h) y_ = f 0(x) 2 2 ∆ [f ](x) Df (x) = lim h h!0 h Derivative of Power function Example: f (x) = x3 In this case, ∆h [f ](x) = f (x + h) − f (x) = (x + h)3 − x3 = x3 + 3x2h + 3xh2 + h3 − x3 = h · (3x2 + 3xh + h2) Hence, 2 2 h · (3x + 3xh + h ) 2 2 2 Df (x) = lim = lim 3x + 3xh + h = 3x h!0 h h!0 In general, for m ≥ 1 integer: 1 D(xm) = mxm− (Forward) Dierence of Power Function Example: f (x) = x3 In this case, 2 ∆f (x) = ∆1 [f ](x) = 3x + 3x + 1 In general, for m ≥ 1 integer: m m ∆(xm) = ∑ xm−k k=1 k because of Newton's binomial theorem. Falling and Rising Factorials Denition The falling factorial (power) is dened for m > 0 by: xm = x(x − 1)(x − 2)···(x − m + 1) The rising factorial (power) is dened for m > 0 by: xm = x(x + 1)(x + 2)···(x + m − 1) Properties xm = (−1)m(−x)m xm+n = xm(x − m)n n! = nn = 1n xm+1 xm = if x 6= m n nk x − m = 1 1 k k! x−m = = (x + 1)m (x + 1)(x + 2)···(x + m) Dierence of falling factorial with positive exponent ∆(xm) = (x + 1)m − xm = (x + 1) · (x ···(x − m + 2)) − (x ···(x − m + 2)) · (x − m + 1) = (x + 1 − (x − m + 1)) · (x ···(x − m + 2)) = m · xm−1 Hence: m m−1 ∆(x ) = mx 8m > 1 Dierence of falling factorial with negative exponent: Example Let's check this formula for negative power: 2 ∆x−2 = (x + 1)− − x−2 1 1 = − (x + 2)(x + 3) (x + 1)(x + 2) (x + 1) − (x + 3) = (x + 1)(x + 2)(x + 3) −2 = (x + 1)(x + 2)(x + 3) = −2 · x−3 Dierence of falling factorial with negative exponent ∆x−m = (x + 1)−m − x−m 1 1 = − (x + 2)···(x + m)(x + m + 1) (x + 1)(x + 2)···(x + m) (x + 1) − (x + m + 1) = (x + 1)(x + 2)···(x + m)(x + m + 1) −m = (x + 1)(x + 2)···(x + m)(x + m + 1) 1 = −mx−(m+ ) = −mx−m−1 Next subsection 1 Finite and Innite Calculus Derivative and Dierence Operators Integrals and Sums Summation by Parts 2 Innite Sums Indenite Integrals and Sums The Fundamental Theorem of Calculus Z Df (x) = g(x) iff g(x)dx = f (x) + C Denition The indenite sum of the function g(x) is the class of functions f such that ∆f (x) = g(x): ∆f (x) = g(x) iff ∑g(x)dx = f (x) + C(x) where C(x) is a function such that C(x + 1) = C(x) for any integer value of x. Denite Integrals and Sums If g(x) = Df (x), then: Z b b g(x)dx = f (x) = f (b) − f (a) a a Similarly: If g(x) = ∆f (x), then: b b ∑g(x)dx = f (x) = f (b) − f (a) a a Denite sums Some observations a 0 ∑a g(x)dx = f (a) − f (a) = a+1 1 ∑a g(x)dx = f (a + ) − f (a) = g(a) b+1 b 1 ∑a g(x)dx − ∑a g(x)dx = f (b + ) − f (b) = g(b) Hence, b b−1 ∑g(x)dx = ∑ g(k) = ∑ g(k) a k=a a6k<b = ∑ (f (k + 1) − f (k)) a6k<b = (f (a + 1) − f (a)) + (f (a + 2) − f (a + 1)) + ··· + (f (b − 1) − f (b − 2)) + (f (b) − f (b − 1)) = f (b) − f (a) Integrals and Sums of Powers If m 6= −1, then: Z n xm+1 n nm+1 xmdx = = 0 m + 1 0 m + 1 Analogous nite case: If m 6= −1, then: n km+1 n nm+1 ∑kmdx = ∑ km = = 0 m + 1 0 m + 1 06k<n Sums of Powers: applications Case m = 1 n2 n(n − 1) ∑ k = 2 = 2 06k<n Case m = 2 Due to k2 = k2 + k1 we get: 3 2 2 n n ∑ k = 3 + 2 06k<n 1 1 1 2 1 = 3 n(n − )(n − ) + 2 n(n − ) 1 2 1 2 3 1 = 6 n( (n − )(n − ) + (n − )) 1 1 2 4 3 = 6 n(n − )( n − + ) 1 1 2 1 = 6 n(n − )( n − ) Taking n + 1 instead of n gives: (n + 1)n(2n + 1) n = 6 Sums of Powers (case m = −1) As a rst step, we observe that: ∆Hx = Hx+1 − Hx 1 1 1 1 1 = 1 + + ::: + + − 1 + + ::: + 2 x x + 1 2 x 1 = = x−1 x + 1 We conclude: b b −1 ∑x dx = Hx a a Sums of Discrete Exponential Functions We have: Dex = ex The nite analogue should have ∆f (x) = f (x). This means: f (x + 1) − f (x) = f (x); that is, f (x + 1) = 2f (x); only possible if f (x) = 2x For general base c > 0, the dierence of cx is: ∆(cx ) = cx+1 − cx = (c − 1)cx cx and the anti-dierence for c 6= 1 is . (c − 1) As an application, we compute the sum of the geometric progression: b cx b cb − ca cb−a − 1 ck = cx dx = = = ca · : ∑ ∑ c − 1 a c − 1 c − 1 a6k<b a Dierential equations and dierence equations Differential equation Solution Difference equation Solution n m Dfn(x) = nfn−1(x) fn(x) = x ∆um(x) = mum−1(x) um(x) = x 0 0 0 0 0 0 fn( ) = [n = ] ; n > um( ) = [m = ] ; m > n m Dfn(x) = nfn−1(x) fn(x) = x ∆um(x) = mum−1(x) um(x) = x fn(1) = 1; n < 0 um(0) = 1=m!; m < 0 1 1 Df (x) = · [x > 0] f (x) = lnx ∆u(x) = · [x 1] u(x) = H x x > x f (1) = 1 u(1) = 1 Df (x) = f (x) f (x) = ex ∆u(x) = u(x) u(x) = 2x f (0) = 1 u(0) = 1 Df (x) = b · f (x) f (x) = ax ∆u(x) = b · u(x) u(x) = cx f (0) = 1 where b = lna u(0) = 1 where b = c − 1 l'Hôpital's rule and Stolz-Cesàro lemma l'Hôpital's rule: Hypotheses Stolz-Cesàro lemma: Hypotheses 1 f (x) and g(x) are both vanishing or both innite 1 u(n) and v(n) are dened at x0. for every value n 2 N. 2 g 0(x) is always positive in 2 v(n) is positive, strictly some neighborhood of x0. increasing, and divergent. l'Hôpital's rule: Thesis Stolz-Cesàro lemma: Thesis 0 f (x) If ∆u(n) , If lim = L 2 , limn!¥ = L 2 R x!x0 g 0(x) R ∆v(n) f (x) u(x) then lim = L. then limn!¥ = L. x!x0 g(x) v(x) Next subsection 1 Finite and Innite Calculus Derivative and Dierence Operators Integrals and Sums Summation by Parts 2 Innite Sums Summation by Parts Innite analogue: integration by parts Z Z u(x)v 0(x)dx = u(x)v(x) − u0(x)v(x)dx Dierence of a product ∆(u(x)v(x)) = u(x + 1)v(x + 1) − u(x)v(x) = u(x + 1)v(x + 1) − u(x)v(x + 1) + u(x)v(x + 1) − u(x)v(x) = ∆u(x)v(x + 1)+ u(x)∆v(x) = u(x)∆v(x) + Ev(x)∆u(x) where E is the shift operator Ef (x) = f (x + 1). We then have the: Rule for summation by parts ∑u∆v dx = uv − ∑Ev∆u dx Why the shift? If we repeat our derivation with two continuous functions f and g of one real variable x, we nd for any increment h 6= 0: f (x + h)g(x + h) − f (x)g(x) = f (x + h)g(x + h) − f (x)g(x + h) + f (x)g(x + h) − f (x)g(x) = f (x)(g(x + h) − g(x)) + g(x + h)(f (x + h) − f (x)) The incremental ratio is thus: f (x + h)g(x + h) − f (x)g(x) g(x + h) − g(x) f (x + h) − f (x) = f (x) · + g(x + h) · h h h So there is a shift: but it is innitesimaland disappears by continuity of g. Summation by Parts (2) Example: n 2k S = ∑k=0 k Taking u(x) = x, v(x) = 2x and Ev(x) = 2x+1: 1 1 ∑x2x dx = x2x − ∑2x+ dx = x2x − 2x+ + C This yields: n n+1 ∑ k2k = ∑ x2x dx k=0 0 n+1 = (x2x − 2x+1) 0 = (n + 1)2n+1 − 2n+2 − (0 · 20 − 2) = (n − 1)2n+1 + 2 Summation by Parts (3) Example: n−1 S = ∑k=0 kHk Continuous analogue: Z x2 Z x2 1 x lnx dx = lnx − · dx 2 2 x x2 1 Z = 2 lnx − 2 x dx x2 1 x2 = 2 lnx − 2 · 2 x2 1 = 2 lnx − 2 Summation by Parts (3) Example: n−1 S = ∑k=0 kHk Taking and 2 2, we get −1 1 , u(x) = Hx vx = x = ∆u(x) = ∆Hx = x x+1 2 1 (x+1) ∆v(x) = x = x , and Ev(x) = 2 .

View Full Text

Details

  • File Type
    pdf
  • Upload Time
    -
  • Content Languages
    English
  • Upload User
    Anonymous/Not logged-in
  • File Pages
    49 Page
  • File Size
    -

Download

Channel Download Status
Express Download Enable

Copyright

We respect the copyrights and intellectual property rights of all users. All uploaded documents are either original works of the uploader or authorized works of the rightful owners.

  • Not to be reproduced or distributed without explicit permission.
  • Not used for commercial purposes outside of approved use cases.
  • Not used to infringe on the rights of the original creators.
  • If you believe any content infringes your copyright, please contact us immediately.

Support

For help with questions, suggestions, or problems, please contact us